Pertanggungjawaban Pidana Praktik Kebidanan Tanpa SIP dalam Perspektif Hukum Pidana Islam - Nova Safitri; Romziatussa'adah Romziatussa'adah; Sarkowi Sarkowi (CV. Doki Course and Training, 2026)
Practicing midwifery without a Practice License (SIP) is not only an administrative violation but can also be a criminal offense if accompanied by medical actions that result in harm to the patient. In such circumstances, the perpetrator can be held criminally liable in accordance with applicable legal provisions. One interesting case to study is Decision Number 1528/Pid.Sus/2024/PN Plg, which sentenced a midwife for practicing without a SIP, resulting in the victim experiencing Stevens-Johnson Syndrome and loss of vision. This study aims to analyze the form of criminal liability in this decision and examine it from the perspective of Islamic criminal law. This research is a normative legal research using a statutory approach, a case approach, and a conceptual approach. Data were obtained through a literature review of laws and regulations, court decisions, scientific literature, and sources of Islamic law, then analyzed qualitatively using prescriptive analysis techniques. The results of the study indicate that criminal liability in Decision Number 1528/Pid.Sus/2024/PN Plg is based on the fulfillment of the elements of an unlawful act, error in the form of negligence (culpa), the ability to be responsible, a causal relationship between the defendant's actions and the losses experienced by the victim, and the absence of justification or excuse. From the perspective of Islamic criminal law, the defendant meets the requirements as a mukallaf and his actions are qualified as jarimah al-khaṭa'. The punishment imposed can be understood as a form of ta'zīr that is in line with the objectives of maqāṣid al-syarī'ah, especially the protection of life (ḥifẓ al-nafs), so that the decision not only guarantees legal certainty, but also supports the protection of patient safety as part of the public interest.